Persistence of irrational decision making in business firms - Nevado, Pedro Picaluga (2022)
To continue with a project, which is failing in an escalating manner, are an economically irrational decision, but one, which contains psychological motivations. The decision-makers display some difficulty in failing to consider the costs arising from the past and keep investing new resources. This is the "Sunk Cost Effect"(SCE), the main subject of this research. Two assumptions were developed. (1) The probability of continuing to invest increases as the non-returned investment (the sunk cost) is greater and is closer to the total planned investment. (2) The decision to go on investing when the sunk cost is stated as a percentage of the planned one is more likely to happen than when the sunk cost is stated in absolute. The hypotheses were tested on two hundred postgraduate students, distributed randomly among eight groups of twenty five students, each independent of one another, using a 2x4 experimental plan, where the independent variables are as follows: the investment carried out, structured according to four different levels and the way in which the investment levels are expressed; in other words as an absolute or percentage value compared to the amount planned for investment. The dependent variable is dichotomous in its answers - yes or no answers - to continue with a lost investment. The results largely confirm the hypotheses formulated. Effectively, the size of the sunk cost and the proximity to the end of the initial objective has an amplifying effect on the decision to persist with the investment, which is not bearing fruit. Moreover, with the exception of extreme situations, the decision-makers reveal a greater willingness to continue with the investment when the problem is presented in proportional terms. The conclusion is that the "Sunk Cost Effect" exists and motivates economically irrational forms of behavior. The decision-maker is a "slave" to past decisions, thus increasing the sunk cost and finds him in difficulties he is unable to overcome. In some situations, the percentage form of expressing the investment seems to more vigorously induce economically erroneous decisions.